The impact of the Affordable Care Act on patient coverage and access to care: perspectives from FQHC administrators in Arizona, California and Texas - Angelo Ercia (BMC Health Services Research, 2021)
Abstract Background The Affordable Care Act (ACA) enabled millions of people to gain coverage that was expected to improve access to healthcare services. However, it is unclear the extent of the policy’s impact on Federally Qualified Health Centers (FQHC) and the patients they served. This study sought to understand FQHC administrators’ views on the ACA’s impact on their patient population and organization. It specifically explores FQHC administrators’ perspective on 1) patients’ experience with gaining coverage 2) their ability to meet patients’ healthcare needs. Methods Twenty-two semi-structured interviews were conducted with administrators from FQHCs in urban counties in 2 Medicaid-expanded states (Arizona and California) and 1 non-expanded state (Texas). An inductive thematic analysis approach was used to analyze the interview data. Results All FQHC administrators reported uninsured patients were more likely to gain coverage from Medicaid than from private health insurance. Insured patients generally experienced an improvement in accessing healthcare services but depended on their plan’s covered services, FQHCs’ capacity to meet demand, and specialist providers’ willingness to accept their coverage type. Conclusion Gaining coverage helped improved newly insured patients’ access to care, but limitations remained. Additional policies are required to better address the gaps in the depth of covered services in Medicaid and the most affordable PHI plans and capacity of providers to meet demand to ensure beneficiaries can fully access the health care services they need.